Assessment of carbon monoxide in exhaled breath using smokerlyzer among in-school adolescents in Osun State: A cross sectional study - Funmito Omolola Fehintola; Adesola Olumide; Adesegun Fatusi; Olayemi Omotade (PLoS ONE, 2026)
Background Smoking is one of the modifiable risk factors of non-communicable diseases and cause of premature death. Surveillance is most often based on self-reported data among adolescents, but few studies have measured exhale breath using Carbon Monoxide in them. This study aimed to measure the prevalence of smoking by measuring exhaled Breath Carbon Monoxide Threshold Levels and Self-Reported Cigarette Smoking in a sample of in-school adolescents in Osun State Nigeria. Methods The study employed a descriptive, cross sectional study design, a multi-stage sampling technique was used to select 616 adolescents from selected secondary schools in Osun State. Smoking status of adolescents were measured using Smokerlyzer, and WHO STEPwise questionnaire. The Cut-off point for current smokers using the exhale level of carbon monoxide (eBco) was ≥ 10parts per million. The collected data were entered into SPSS version 20 software for statistical analysis. Multivariable logistic regression analyses were done to identify the true effect of predictor variables on the outcome variable. Statistical significance was declared at a p-value < 0.05. Findings Smoking by self- report was 80 (13.0%) while the smokerlyzer detected 168 (27.3%) current smokers. Cohen’s κ = 0.063 (smokerlyzer) showed poor agreement between self-report and objective measures. Determinants of smoking include older age (AOR = 1.59, CI = 1.01–2.34), class level, compared with students in JSS1, SSS1 (AOR = 0.14, 95% CI: 0.07–0.26), and SSS2 (AOR = 0.46, 95% CI: 0.23–0.78) were significantly less likely to smoke. Rank regression analysis revealed that age was negatively associated with the rank of smoking status (B = −0.10, p = 0.008). Conclusion Prevalence of smoking using smokerlyzer was higher compared to self-report among in-school adolescents. The study identified older age and class as important predictors of smoking Targeted health education should be done in schools to enhance smoking cessation.